Epigraphy and History of The Mausoleum Of Abu Bakr Kaffal Shashi - Nematullo Mukhamedov; Nurulloh Turambetov (Penerbit Jurnal Indonesia, 2024)
The Hast Imam Complex (Hazrati Imam) is one of the most significant cultural treasures of Tashkent, serving as the religious heart of the capital. It developed around the tomb of the great saint and the first imam of Tashkent, Abu Bakr Muhammad Kaffal Shashi. Abu Bakr Muhammad Kaffal Shashi was one of the early imams of the Muslim world, a renowned scholar, and an expert in the Quran, hadith, Islamic law, and lexicology. He passed away in 976/77, and his grave became a revered pilgrimage site. Alongside Imam al-Bukhari, at-Tirmidhi, and al-Maturidi, Imam Abu Bakr Kaffal Shashi (904-977) holds a special place in the Islamic world. His contemporaries respectfully referred to him as